Urea and salt as supplementary diet for crossbreed milk cows - César Roberto Viana Teixeira; Rogério de Paula Lana; Luciana Navajas Rennó; Cristina Mattos Veloso; Juliana do Carmo Carvalho; André Azevedo de Menezes (Acta Scientiarum. Animal Sciences, 2015)
This study aimed to evaluate the use of supplementary feed with different percentages of urea and mineral salt for crossbred milk cows. Ten animals were used, mean body weight 480 kg ± 9,7, distributed in a 5 x 5 double Latin square, with treatments of supplements with different urea and mineral salt percentages, namely, 10:10; 10:20; 20:10 and 20:20, completed to 100% with corn meal. Data underwent statistical analysis by SAS at 0.05 significance level. The use of supplements increased (p < 0.05) the total dry matter (DM) intake of diet. The increase in the level of urea in the supplement decreased DM intake of supplement. The use of supplements increased (p < 0.05) DM digestibility. The treatments with presence of supplement showed higher (p < 0.05) milk production. Supplemented diets may be used to correct nutritional deficiencies of sugar cane, with higher intake, digestibility and milk production. Treatments with 20% urea in the composition of the supplement caused a lower DM consumption with the same performance in the animals. The above-mentioned treatments had the best efficiency.